An observational study to evaluate the maternal and neonatal outcome of forceps delivery in a tertiary care government hospital of a cosmopolitan city of India - Lamba, Akanksha; Kaur, Ramanjeet; Muzafar, Zulaihuma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Operative vaginal delivery using obstetric forceps is a practice that dates back several centuries. Modern obstetrics practice has witnessed an increase in the caesarean section rates. The goal of forceps delivery is to mimic spontaneous vaginal birth, thereby expediting delivery with a minimum of maternal or neonatal morbidity. The main objective of study was to evaluate the maternal and neonatal outcome of forceps assisted deliveries in a tertiary care hospital over a period of one year. Methods: This retrospective observational study was done in obstetrics and gynecology department of Kasturba Hospital, Delhi from November 2014 to October 2015. Seventy cases of forceps delivery were studied for maternal outcome such as injuries, postpartum hemorrhage, need of blood transfusion and fetal outcome such as birth weight, Apgar scores at birth, neonatal intensive care unit admissions, injury, still births and neonatal mortality. Results: 68.5% of patients requiring forceps application were primigravida. The most common indication was fetal distress (54.2%) followed by maternal exhaustion. The most common maternal complication was extension of episiotomy (10), 1 case of uterine rupture which was in a previous lower segment caesarean section case, 2 complete perineal tears, 3 cases of vaginal and cervical lacerations. Postpartum hemorrhage requiring blood transfusion occurred in 4 cases. A total of 19 babies had poor Apgar scores and 9 of them needed NICU admission. There were 3 cases of still births and 2 of early neonatal deaths. Conclusions: The second stage interventions are associated with increased maternal and neonatal morbidity. Judicial use forceps under close supervision and with proper expertise can reduce the caesarean section rates.